Perhitungan Panas pada Pemanasan Preform PET di Unit Heater Blow molding PT. Sinar Sosro - Saragih, Koko Pratama; Tarigan, Ratna Kristina; Putri, Jaihy Sabana (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2024)
Blow molding is a bottle molding process aimed at forming PET preforms into PET bottles. This process is highly influenced by heat, which functions to soften the PET preform to facilitate its formation in the subsequent stages. Therefore, temperature control is a critical factor in this process. The energy balance method was used to calculate the heat required during the preform heating process in the heater unit. The results showed that the heat required during the preform heating process in the heater unit was 6,441,218.72 cal/hour, 6,531,114.65 cal/hour, and 6,486,129.51 cal/hour. The heat transfer efficiency of the heater for the preform was 90.74%, 92.00%, and 91.37%, respectively.